Avaliaç\~ao da produç\~ao energética de um projeto eólico offshore no litoral fluminense - Jose Francisco Moreira Pessanha; Luis Alberto Toscano Medrano; Mário Jorge Mendonça; Albert Cordeiro Geber de Melo; Maria Elvira Pi\~neiro Maceira; Victor Andrade de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This work presents a Bayesian approach for inferring the capacity factor of an offshore wind farm. The application of the proposed methodology is illustrated through a case study of a wind power offshore project located on the northern coast of the Rio de Janeiro State.
Keywords: Q42; Q47; Q54; 330; offshore wind power; Bayesian approach; MCMC; capacity factor